General Equation for Advance and Recession of Water in Border Irrigation†. (17th April 2019) - Chari, Mohammad Mahdi; Davary, Kamran; Ghahraman, Bijan; Ziaei, Ali Naghi
Abstract: Advance and recession curves are of great importance for assessing the performance of border irrigation. In recent years, scaling techniques have helped to reduce the required measurements and to provide formulation of soil–water relations. The purpose of this study was to develop an invariant equation for calculating advance and recession curves in border irrigation using scaling techniques. The kinematic wave model and the Philip infiltration equation were used to simulate border irrigation. Scale factors were defined such that the kinematic wave equation remained independent of the initial and boundary conditions of the soil. Scaled advance and recession curves showed certain patterns, which led us to introduce a power and a binomial equation for advance and recession phases, respectively. The scaled equations were applied on 25 vegetated and non‐vegetated borders. Four performance indices were calculated for each border, including application efficiency ( E a ), deep percolation ratio (DPR), tail water ratio (TWR) and water requirement efficiency ( E r ). Results showed that the maximum differences between measured and estimated values were 4% for E a, 9% for DPR and 4% for E r . Considering the simplicity and soil‐condition independence of the proposed method, it can be concluded that scaled advance and recession curves could provide a reasonable estimate of border irrigation performance. © 2019 John Wiley & Sons, Ltd. Résumé: Les courbes de progression et de récession revêtent une grande importance pour l'évaluation des performances de l'irrigation par planches. Ces dernières années, les techniques d'analyse d'échelle ont permis de réduire les mesures requises et de formuler les relations sol–eau. Le but de cette étude était de développer une équation invariante pour le calcul des courbes de progression et de récession dans l'irrigation par planches à l'aide de techniques d'analyse d'échelle. Le modèle d'onde cinématique et l'équation d'infiltration de Philip ont été utilisés pour simuler l'irrigation par planches. Les facteurs d'échelle ont été définis de telle sorte que l'équation d'onde cinématique reste indépendante des conditions initiales et limites du sol. Les courbes de progression et de récession échelonnées montrent certains comportements, ce qui a conduit à introduire une équation de puissance et une équation binomiale pour les phases de progression et de récession, respectivement. Ces équations ont été appliquées sur 25 bordures végétalisées et non végétalisées. Quatre indices de performance ont été calculés pour chaque planche, notamment l'efficacité d'application ( E a ), le rapport de percolation profonde (DPR), le rapport d'eau de queue (TWR) et l'efficacité des besoins en eau ( E r ). Les résultats ont montré que la différence maximale entre les valeurs mesurées et estimées était de 4% pour E a, 9% pour DPR et 4% pour E r . Compte tenu de la simplicité et de l'indépendance des conditions de sols de la méthode proposée, on peut en conclure que les courbes de progression et de récession à l'échelle pourraient fournir une estimation raisonnable des performances de l'irrigation par planche. © 2019 John Wiley & Sons, Ltd.